2009
DOI: 10.1088/0268-1242/24/12/125008
|View full text |Cite
|
Sign up to set email alerts
|

Free-standing gallium nitride Schottky diode characteristics and stability in a high-temperature environment

Abstract: Schottky diodes have been fabricated using low-resistivity n-type free-standing GaN substrates with a reduced defect density lowly doped n-type epi-layer and an Ni/Ti/Pt/Au Schottky contact metalization. A thermionic field emission current transport mechanism was identified with a Schottky barrier height of about 0.75 eV and a diode ideality of 1.1 measured at 25 • C, both of which increase with measurement temperature up to 200 • C. The diodes were subjected to long-term testing under forward current (1.3 A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…the optimal temperatures for highest SBHs [39][40][41][42]. There was a significant increase of Ni/ Ti/Pt/Au's SBH at an annealing temperature of 400 °C [39].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…the optimal temperatures for highest SBHs [39][40][41][42]. There was a significant increase of Ni/ Ti/Pt/Au's SBH at an annealing temperature of 400 °C [39].…”
Section: Resultsmentioning
confidence: 94%
“…Hence, the degradation of the Ni/Pt/Au metallization can be attributed to the presence of It has been reported that Ni/Ti/Pt/Au, Ni/Mo, and Ni/Au Schottky contacts on n-type GaN under thermal annealing have the similar trends, i.e. the optimal temperatures for highest SBHs [39][40][41][42]. There was a significant increase of Ni/ Ti/Pt/Au's SBH at an annealing temperature of 400 °C [39].…”
Section: Resultsmentioning
confidence: 98%
“…Research by Luther et al 120 showed that Pt Schottky contacts can maintain at 400 C for 500 h without degradation. O'Mahony et al 119 studied Ni-based Schottky contacts and found that under a forward current of 1.3 A/cm 2 or a reverse bias of À3.5 V while stored at 300 C in an N 2 environment for 466 h, the diodes exhibit a drift of less than 10% in both the ideality factor and barrier height. Despite these cases, more research is still needed to understand the long-term operating performance.…”
Section: B High Temperature Performancementioning
confidence: 99%
“…Its high carrier mobility and active optical properties have made germanium (Ge) be considered as a promising material for semiconductor devices. There are a number of fledgling technologies being developed that require the epitaxial growth of Ge films on crystalline silicon (c-Si) substrates, such as Ge on Si photodetectors for near infrared (1.3-1.55 m) sensing [8][9][10], Ge lasers [11], and monolithic integration of III-V compound semiconductor devices on c-Si 2 International Journal of Photoenergy [12][13][14][15]. However, the difficulty of growing epitaxial Ge on a Si substrate lies in the 4.2% lattice mismatch between Ge and Si.…”
Section: Introductionmentioning
confidence: 99%